Analisis Penerapan Dan Pengembangan Manajemen Operasional Desain Produk Dan Rantai Pasokan Pada UKM Kelompok Pahari Palangka Raya - Kuwing Baboe; Andrie Elia; Thea Farina; Maria Haryulin Astuti (Edunomics Journal, 2021)
This study uses a qualitative approach and the type of research used is descriptive research. Types of data are primary data and secondary data. Operational management of product design that is appropriate to increase sales results of SME Rattan Group Pahari Palangka Raya products by applying eight aspects of product design (form, features, performance, suitability, durability, reliability, style, and ease of repair) with priority on products and prices. marketed. The proper operational management of the supply chain to increase the output of the SME Rattan of the Pahari Palangka Raya Group is by implementing a multi-supplier supply chain strategy with priority on family, cost, quality and distance. The driving factor for the progress of the Pahari Palangka Raya Rattan SME Group is having a business license, emphasizing product quality and quality, affordable prices, in terms of motifs, sizes and designs that can be adjusted according to consumer desires, and timeliness of processing. While the inhibiting factors for the progress of this business are the emergence of competitors, differences in prices with other products, and the products offered have in common with other products.